A literature-driven method to calculate similarities among diseases. Issue 2 (November 2015) - Kim, Hyunjin; Yoon, Youngmi; Ahn, Jaegyoon; Park, Sanghyun
Highlights We proposed a novel method which calculates disease–disease similarity. The proposed method can be used in constructing of disease network. The proposed method discovered the largest number of answer disease pairs and showed lowest p-value when compared with other comparable methods. The proposed method can provide an insight of relationship between diseases.